2009
DOI: 10.1038/ejcn.2008.63
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment in the Avon Longitudinal Study of Parents and Children

Abstract: Objectives: To describe the use of dietary assessment methods in a cohort study. Subjects: The Avon Longitudinal Study of Parents and Children (ALSPAC) based in Bristol, UK, a cohort of children born in 1991/1992 and their parents. Methods and Results: Data were collected about maternal and paternal diet, breastfeeding, weaning and childhood diet by both food frequency questionnaire (FFQ) and unweighed diet records (children only). Other questionnaires have covered socioeconomic background and eating behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 22 publications
1
65
0
Order By: Relevance
“…Similar to other cohort studies (42)(43)(44) , dietary data in BiB1000 were collected by parent-reported FFQ. This method is prone to overestimate intake but is a standard, feasible approach in large samples (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other cohort studies (42)(43)(44) , dietary data in BiB1000 were collected by parent-reported FFQ. This method is prone to overestimate intake but is a standard, feasible approach in large samples (45) .…”
Section: Discussionmentioning
confidence: 99%
“…The estimated diary has been used in a number of studies in the UK, such as the MRC National Survey of Health and Development (1946 British Birth Cohort) (9) , the EPIC Norfolk study (10) and the UK Women's Cohort Study in Leeds (over 35 000 women) (11) . The method is also used in children, most notably in the Avon Longitudinal Study of Parents and Children cohort at ages 4, 8 and 18 months, 3, 7, 10 and 14 years (12) . The repeat 24 h recall method is used in the National Health and Nutrition Examination Survey in the United States and in the Low Income Diet and Nutrition Survey, conducted in 2004-05 (13) .…”
Section: Dietary Assessment In the National Diet And Nutrition Surveymentioning
confidence: 99%
“…Food items in questionnaires were selected by a qualified research dietitian (PE) to reflect those commonly fed to infants and toddlers at the time. The 6-mo questionnaire covered the period from birth to 6 mo, whereas the 15-mo questionnaire covered the period from 6 to 15 mo, and the 24-mo questionnaire covered the period from 15 to 24 mo (20,21). Caregivers were asked to document the frequency of intake of foods nowadays.…”
Section: Dietary Intakementioning
confidence: 99%